2020
DOI: 10.1002/smtd.202000834
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Level Insight into Correlation between Surface Defects and Stability of Methylammonium Lead Halide Perovskite Under Controlled Humidity

Abstract: Perovskite‐based photovoltaics (PVs) have garnered tremendous interest, enabling power conversion efficiencies exceeding 25%. Although much of this success is credited to the exploration of new compositions, defects passivation and process optimization, environmental stability remains an important bottleneck to be solved. The underlying mechanisms of thermal and humidity‐induced degradation are still far from a clear understanding, which poses a severe limitation to overcome the stability issues. Herein, in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 70 publications
(39 reference statements)
4
49
0
Order By: Relevance
“…Local chemical environments of en cations in the FAPbBr 3 perovskite framework are best consolidated by 1D and 2D solid-state NMR spectroscopy (ssNMR) measurements and analysis. Specially, ssNMR spectroscopy has recently been applied to characterize local structures and intermolecular interactions at sub-nm to nm length scale in optoelectronic materials. Figure compares the 1D and 2D 1 H ssNMR spectra of pristine FAPbBr 3 and en substituted FAPbBr 3 at different stoichiometric concentrations, whereby signals correspond to distinct 1 H sites: 4.1 (−CH 2 –, en ), ∼7.5 (−NH 3 + , en and FA + ), and 8.1 ppm (CH, FA + ) are color coded as depicted in the schematic structures. Of particular interest is the broad line shape associated with the 1 H signal at ∼4.1 ppm in the 1D spectra of 33% en and 44% en as compared to the narrow feature in 12% en , indicating that the en cations exhibit different local chemical environments in the FAPbBr 3 framework.…”
Section: Resultsmentioning
confidence: 99%
“…Local chemical environments of en cations in the FAPbBr 3 perovskite framework are best consolidated by 1D and 2D solid-state NMR spectroscopy (ssNMR) measurements and analysis. Specially, ssNMR spectroscopy has recently been applied to characterize local structures and intermolecular interactions at sub-nm to nm length scale in optoelectronic materials. Figure compares the 1D and 2D 1 H ssNMR spectra of pristine FAPbBr 3 and en substituted FAPbBr 3 at different stoichiometric concentrations, whereby signals correspond to distinct 1 H sites: 4.1 (−CH 2 –, en ), ∼7.5 (−NH 3 + , en and FA + ), and 8.1 ppm (CH, FA + ) are color coded as depicted in the schematic structures. Of particular interest is the broad line shape associated with the 1 H signal at ∼4.1 ppm in the 1D spectra of 33% en and 44% en as compared to the narrow feature in 12% en , indicating that the en cations exhibit different local chemical environments in the FAPbBr 3 framework.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for E a reduction on RH is still obscure and complex in nature. It has been reported that monohydrated CH 3 NH 3 PbI 3 ·H 2 O or dehydrated (CH 3 NH 3 ) 4 PbI 6 ·2H 2 O intermediate phase will form at high humidity (80% RH) . These intermediate phases are unstable due to CH 3 NH 3 + deprotonation, resulting in the degradation of CH 3 NH 3 PbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that monohydrated CH 3 NH 3 PbI 3 •H 2 O or dehydrated (CH 3 NH 3 ) 4 PbI 6 •2H 2 O intermediate phase will form at high humidity (80% RH). 46 These intermediate phases are unstable due to CH 3 NH 3 + deprotonation, resulting in the degradation of CH 3 NH 3 PbI 3 . It is also proposed that water molecules can incorporate in the perovskite crystal lattice to form stable and reversible waterintercalated phases at moderate RH.…”
Section: Resultsmentioning
confidence: 99%
“…Several in situ and ex situ characterization techniques have been used to study phase stability in FA-based and FA-rich perovskites. ,, It has been suggested that the grain boundaries are susceptible to water-ingress, leading to α → δ phase transformation: this reaction is reported to endure between hours to months to complete, as different studies report the different synthetic, fabrication, and aging conditions. Notably, photothermal induced resonance (PTIR with a spatial resolution of ∼100 nm) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) techniques have been used to characterize the humidity-induced phase transformations and to probe surface and subsurface compositions in FA-rich perovskites . Solid-state NMR (ssNMR) spectroscopy is a local probe that provides information on the structures and dynamics in hybrid perovskites with site-specificity: for example, ssNMR techniques have been used to gain insight into chemical doping, cation-ordering and dynamics, interfacial engineering, phase stability, and degradation products. However, a precise understanding of how water molecules induce a “catalysis-like” transformative reaction, that is, how water reacts without directly integrating into the initial perovskite (α) or the final nonperovskite (δ) FAPbI 3 structures, and insight into the nature of the intermediate phases is lacking, which necessitates further investigation. Because this reaction contributes to the FAPbI 3 instability that rigorously affects the performance of solar cells, it is crucially important to understand the molecular origins of the phase transition, kinetic, and thermodynamic factors, which influence the degradation of hybrid perovskites …”
mentioning
confidence: 99%